Relationship between serum sodium level and sepsis-induced coagulopathy - Han, Yanyu; Duan, Jianfeng; Chen, Ming; Huang, Shijie; Zhang, Beiyuan; Wang, Yan; Liu, Jiali; Li, Xiaoyao; Yu, Wenkui (Frontiers in Medicine, 2024)
Purpose A discussion about the correlation between the level of serum sodium and sepsis-induced coagulopathy (SIC)[ SIC, sepsis-induced coagulopathy]. Materials and Methods A retrospective analysis was conducted on sepsis patients who were admitted to the Intensive Care Unit (ICU) of Nanjing Drum Tower Hospital from January 2021 to December 2022. Based on the presence of coagulation disorders, the patients were divided into two groups: sepsis-induced coagulopathy (SIC) and non-sepsis-induced coagulopathy (non-SIC) groups. We recorded demographic characteristics and laboratory indicators at the time of ICU admission, and analyzed relationship between serum sodium level and SIC. Results 125 patients with sepsis were enrolled, among which, the SIC and the non-SIC groups included 62 and 63 patients, respectively. Compared to patients in the non-SIC group, the level of serum sodium of those in the SIC was significantly higher (p < 0.001). Multi-factor logistic regression showed serum sodium level was independently associated with SIC (or = 1.127, p = 0.001). Pearson’s correlation analysis indicated that the higher the serum sodium level , the significantly higher the SIC score was (r = 0.373, p < 0.001). Additionally, the mortality rate of patients with sepsis in the ICU were significantly correlated with increased serum sodium levels (p = 0.014). Conclusions An increase in serum sodium level was independently associated with an increased occurrence of SIC and also associated with the poor prognosis for patients with sepsis.